2007
DOI: 10.1152/ajprenal.00462.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of the TRPV4 channel as a sensor of flow and osmolality in renal epithelial cells

Abstract: Gain/loss of function studies were utilized to assess the potential role of the endogenous vanilloid receptor TRPV4 as a sensor of flow and osmolality in M-1 collecting duct cells (CCD). TRPV4 mRNA and protein were detectable in M-1 cells and stably transfected HEK-293 cells, where the protein occurred as a glycosylated doublet on Western blots. Immunofluorescence imaging demonstrated expression of TRPV4 at the cell membranes of TRPV4-transfected HEK and M-1 cells and at the luminal membrane of mouse kidney CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
179
1
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 78 publications
(108 reference statements)
17
179
1
1
Order By: Relevance
“…[Ca 2ϩ ] i Measurements-Intracellular calcium levels were measured in cells of the split-opened ASDNs using Fura-2 fluorescence ratiometric imaging as described previously (32,33). Split-opened ASDNs were loaded with Fura-2 by incubation with 2 M Fura-2/AM in a bath solution for 40 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[Ca 2ϩ ] i Measurements-Intracellular calcium levels were measured in cells of the split-opened ASDNs using Fura-2 fluorescence ratiometric imaging as described previously (32,33). Split-opened ASDNs were loaded with Fura-2 by incubation with 2 M Fura-2/AM in a bath solution for 40 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Although the TRPV4 channel can be activated by a wide range of stimuli, it has been shown to be particularly sensitive to physical alterations of the cellular microenvironment as it can be activated by variations in osmolality (1,2), fluid shear stress/flow (3)(4)(5)(6), pressure (7), and moderate heat (8,9). Hence, it is becoming evident that the channel may play a critical role in sensing and/or transducing changes in the microenvironmental physical state, at least in some cells.…”
Section: Trpv4mentioning
confidence: 99%
“…Recent studies, however, point to an apparent role of TRPV4 as a sensor of fluid shear stress or fluid flow in renal cells and tissues. Indeed, our laboratory recently demonstrated that endogenous TRPV4 in M-1 collecting duct cells is activated by increases in shear stress/fluid flow, a response that is abolished following siRNA knockdown of TRPV4 (3,4). Furthermore, Suzuki and co-workers (14) have shown that flow-dependent K ϩ secretion, a Ca 2ϩ -dependent process utilizing the maxi-K channel (11)(12)(13), is essentially abolished in TRPV4 knock-out animals.…”
Section: Trpv4mentioning
confidence: 99%
“…It revealed a temperature-induced potentiation or switching on of a channel signaling pathway. It has also been demonstrated that TRPV4 is activated by shear stress in native collecting duct cells [26].…”
Section: Trpv4mentioning
confidence: 99%